Woody vegetation, endemism and conservation status in the seasonally dry forests of Jaen, Peru - Marcelo Peña, José Luis (2008)
Eight relictual areas of seasonally dry tropical forest (SDTF) from the surroundings Jaen city, in Cajamarca, were investigated using a rapid inventory technique. The areas were situated between 5°38’ and 5°48’ S and 78°41’ and 78°48’ W, and between 615 and 1100 m altitude. A total of 151 species, 103 genera and 40 families of woody plants were recorded. The area shows high diversity of woody plants in comparison with other neighbouring regions. Most notable is its endemism, which is the highest in the region of southwest Ecuador and Peru. However, the area is seriously threatened by demand for firewood and the need for land for crops, large cattle farms and housing.